g-C3N4/TiO2 Nanofiber Hybrid Photocatalyst with Effective Photogenerated Charge Separation Rate and Enhanced Activity - Zhao1, Y.F.; Zhang2, J.; Wang2, Y.J.; Hu3, S.Z. (Asian Journal of Chemistry, 2014)
g-C3N4/TiO2 nanofiber hybrid materials were prepared by a simple hydrothermal method. X-Ray diffraction, UV-visible spectroscopy, scanning electron microscope, electrochemical impedance spectra and X-Ray photoelectron spectroscopy were used to characterize the prepared catalysts. The results indicated that the mass percentage of TiO2 nanofiber and g-C3N4 strongly influenced the optical property and separation efficiency of photogenerated electrons and holes. Ti(0.5)CN(0.5) exhibited the highest photogenerated charge separation rate and the best photocatalytic performance on Rhodamine-B degradation. The reaction rate constant of Ti(0.5)CN(0.5) was 0.004 min-1, which is about 20 and 2 times as high as that of single TiO2 nanofiber and g-C3N4. The possible mechanism was proposed.